2008
DOI: 10.1021/jm800257s
|View full text |Cite
|
Sign up to set email alerts
|

Novel Analogues of Istaroxime, a Potent Inhibitor of Na+,K+-ATPase: Synthesis and Structure−Activity Relationship

Abstract: We report the synthesis and biological properties of novel inhibitors of the Na(+),K(+)-ATPase as positive inotropic compounds. Following our previously described model from which Istaroxime was generated, the 5alpha,14alpha-androstane skeleton was used as a scaffold to study the space around the basic chain of our lead compound. Some compounds demonstrated higher potencies than Istaroxime on the receptor and the (E)-3-[(R)-3-pyrrolidinyl]oxime derivative, 15, was the most potent; as further confirmation of ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 15 publications
(28 reference statements)
1
26
0
Order By: Relevance
“…5,8 This assertion is supported by comparison of the few available experimental inhibitory data of the correlated E/Z mixture, the pure E and the Z isomers. In the following examples, both the inhibition value of the E isomer and the one of the mixture are always higher than the value of the Z isomer: 5 its E isomer (2.0 lM) 4 and its Z isomer (12.0 lM).…”
Section: D-quantitative Structure-activity Relationshipmentioning
confidence: 81%
See 3 more Smart Citations
“…5,8 This assertion is supported by comparison of the few available experimental inhibitory data of the correlated E/Z mixture, the pure E and the Z isomers. In the following examples, both the inhibition value of the E isomer and the one of the mixture are always higher than the value of the Z isomer: 5 its E isomer (2.0 lM) 4 and its Z isomer (12.0 lM).…”
Section: D-quantitative Structure-activity Relationshipmentioning
confidence: 81%
“…The choice of the three different amines was based on their potencies and different structures, as reported in a recent study about the systematic variation of the oximic chain present in Istaroxime. 8 The 2-aminoethyl oxime was chosen as reference chain since it is present in Istaroxime and as example of primary amine with high potency. The (3R)-3-pyrrolidinyloxyimino chain was used because some cyclic amines on the oximic group at position 3 gave compounds with a higher inhibitory potency than the linear amine analogues (in particular (E,Z)-3-[(3R)-3-pyrrolidinyloxyimino]androstane-6,17-dione, compound C, was found to be about four times more potent than Istaroxime) and as example of a secondary cyclic amine.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Searching for these molecules has yielded istaroxime analogs with better activity, and even structure-activity relationships have been found. 45,46 Further, a high-throughput fluorescence resonance energy transfer assay has been used to find allosteric SERCA2a activators capable of decreasing SERCA2a/PLN-derived fluorescence resonance energy transfer. 47 In this study, several compounds previously reported to correct aberrant Ca 2+ regulation in HF were shown to activate SERCA2a activity, thus validating the mechanism of action for these drugs.…”
mentioning
confidence: 99%